2018
DOI: 10.1111/1541-4329.12148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Game‐Based e‐Learning Module on Undergraduate Food Science Students’ Planned Behaviors Concerning Good Manufacturing Practices

Abstract: Understanding the role of food science education in developing undergraduate students' intentions to implement Good Manufacturing Practices (GMPs) may be a key strategy in developing the workforce's implementation of GMPs and other food safety programs. Previous research has demonstrated the effects of educational interventions on planned food safety behaviors in various settings; however, none have studied GMPs interventions and college students. This study applied the Theory of Planned Behavior (TPB) to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Hinsz and Nickell (17) and Phillip and Anita (29) also reported that attitudes predicted food safety intentions of workers in their studies at a poultry processing facility and food handlers in hospitality settings, respectively. However, undergraduate students' attitudes did not predict their food safety intentions in two other studies (24,33), which may perhaps be explained by an apparent social desirability bias (28).…”
Section: Instrumental and Experiential Attitudes Self-efficacies And Intentionsmentioning
confidence: 72%
See 1 more Smart Citation
“…Hinsz and Nickell (17) and Phillip and Anita (29) also reported that attitudes predicted food safety intentions of workers in their studies at a poultry processing facility and food handlers in hospitality settings, respectively. However, undergraduate students' attitudes did not predict their food safety intentions in two other studies (24,33), which may perhaps be explained by an apparent social desirability bias (28).…”
Section: Instrumental and Experiential Attitudes Self-efficacies And Intentionsmentioning
confidence: 72%
“…However, Hinsz and Nickell (17) reported the opposite. Mullan and Wong (24) reported that perceived behavioral control was a significant predictor of college students' food safety intentions, but in contrast Stevenson et al (33) reported that perceived behavioral control was a significant predictor of college students' intentions only after a food safety educational intervention and not before. These results corroborate an observation from a meta-analysis of behavioral studies that perceived behavioral control irregularly predicts intentions (3).…”
Section: Instrumental and Experiential Attitudes Self-efficacies And Intentionsmentioning
confidence: 93%
“…Also other improvement can be implemented to enhance the learning process in this course, for example, the implementation of gamebased e-learning activity about food additives or other contents within the course. Gaming have been shown a significantly increased college students' knowledge, for example about Good Manufacturing Practices (Stevenson et al, 2018). Eventually, stories may also be part of games, and, in the field of education, the application of games supporting learning processes has been developed into an increasing body of research (Bidarra et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers strongly believe in gamification to drive learning, interaction, collaboration, skill acquisition, understanding content, and changing attitude or behavior. Compared to traditional practices, they support effectiveness in engagement, motivation, stimulating curiosity, autonomy, and satisfaction [5,6,34,38,[40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%